2016
DOI: 10.1016/j.ijwd.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prolactin levels in patients with newly diagnosed pemphigus vulgaris and its correlation with pemphigus disease area index

Abstract: BackgroundProlactin is a hormone; in addition to it known roles, it has immunomodulatory effects on lymphocytes maturation and immunoglobulins production. Hyperprolactinemia has been demonstrated in various autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis, type I diabetes mellitus, and Graves’ disease. In view of the prolactin immunomodulatory roles, studying prolactin levels in pemphigus as an autoimmune blistering disease may introduce new ways of understanding disease etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A small study demonstrated higher levels of the PRL-R in patients with alopecia areata compared to controls, and levels of the PRL-R were correlated with disease severity [154]. Patients with pemphigus vulgaris have also been shown to have higher PRL compared with controls [155]. The pathophysiological significance of these findings remains to be elucidated.…”
Section: Other Autoimmune Disordersmentioning
confidence: 99%
“…A small study demonstrated higher levels of the PRL-R in patients with alopecia areata compared to controls, and levels of the PRL-R were correlated with disease severity [154]. Patients with pemphigus vulgaris have also been shown to have higher PRL compared with controls [155]. The pathophysiological significance of these findings remains to be elucidated.…”
Section: Other Autoimmune Disordersmentioning
confidence: 99%
“…In another study, Jacobi et al 17 found mean prolactin level 17.4±15.1 ng/ml. Lajevardi et al 18 also found that mean prolactin (PRL) level was 15.60±11.72ng/ml. Ghandi et al 19 found mean serum PRL level 15.9±14.1 ng/ml.…”
Section: Resultsmentioning
confidence: 94%